Empowering Patient Safety: Assessment of Adverse Drug Reaction Knowledge and Practice Among Pharmacy Professionals - Josipa Bukić; Dario Leskur; Toni Durdov; Joško Božić; Darko Modun; Ana Šešelja Perišin; Daniela Ančić; Martina Šepetavc; Ante Mihanović; Doris Rušić (Pharmacy, 2024)
Despite technological advancements, healthcare professionals must actively prioritize patient safety. Reporting adverse drug reactions is a critical aspect of this responsibility, and the most accessible healthcare providers, community pharmacists, and pharmacy technicians play a key role. Therefore, this study assessed their knowledge and practices regarding adverse drug reaction reporting in Croatia. A total of 180 participants were included. Pharmacists demonstrated significantly better knowledge than technicians (94.78 vs. 73.97, p = 0.024). Chronic medication users also showed greater understanding compared to non-users (104.96 vs. 85.39, p = 0.021). Knowledge improved with the number of adverse drug reactions reported, and most participants (72.78%) had reported adverse drug reactions. Pharmacists were 83.60% more likely to report adverse drug reactions than technicians (p < 0.001). These findings reveal a gap in pharmacy technicians’ integration into pharmacovigilance, underscoring a need to strengthen their role in adverse drug reaction reporting and patient safety.